ENGAGING WITH THE UN HUMAN RIGHTS COUNCIL"S UNIVERSAL PERIODIC REVIEW MECHANISM AS AN ACADEMIC - DOI 10.5935/2448-0517.20200042 - Storey, Alice (Juris Poiesis - Qualis A3, 2020)
Non-governmental organisations are vital to the progression and realisation of global human rights. In particular, they play a pivotal role as "Stakeholders" in the United Nations Human Rights Council"s (UNHRC) Universal Periodic Review (UPR). The UPR is an innovative mechanism with the aim of ensuring the protection and promotion of human rights across the world. Stakeholders can submit individual reports, based upon experience and research, detailing both problem areas and advances in human rights on the ground in UN Member States. This paper draws upon the experiences of submitting Stakeholder reports from an academic institution through the "UPR Project at BCU," and the recognition it has achieved to date through citations in the USA"s final 2020 Stakeholder Report. This paper also seeks to encourage further academic input to the UPR process through the submission of individual Stakeholder reports, in order for scholarly research to support human rights discourse and seek to influence change on the ground.